The effect and safety of dressing composed by nylon threads covered with metallic silver in wound treatment - Brogliato, Ariane R (Int Wound J, 2012)
Silver is used worldwide in dressings for wound management. Silver has demonstrated great efficacy against a broad range of microorganisms, but there is very little data about the systemic absorption and toxicity of silver in vivo. In this study, the antimicrobial effect of the silver‐coated dressing (SilverCoat®) was evaluated in vitro against the most common microorganisms found in wounds, including Pseudomonas aeruginosa, Candida albicans, Staphylococcus aureus, Methicillin‐resistant Staphylococcus aureus and Klebsiella pneumoniae. We also performed an excisional skin lesion assay in mice to evaluate wound healing after 14 days of treatment with a silver‐coated dressing, and we measured the amount of silver in the blood, the kidneys and the liver after treatment. Our data demonstrated that the nylon threads coated with metallic silver have a satisfactory antimicrobial effect in vitro, and the prolonged use of these threads did not lead to systemic silver absorption, did not induce toxicity in the kidneys and the liver and were not detrimental to the normal wound‐healing process.